Contribution to Andean flora from Oyón District , Lima, Peru - Kahn, Francis (2016)
In this paper, the inventory of vascular plants of high mountains (altitudes of 4000-4810 m) from northeast Oyon district, Lima, Peru is presented. Specimens were collected during March to May 2014 and 2015 and September to November 2015. 47 families, 112 genera and 181 species are reported, of which 94 were the first record for Lima region. For each species are given collector names, collect number and elevation. New local botanical inventories are needed for better evaluating the diversity, species distribution patterns and endemism in the high Andean vegetation.